2020
DOI: 10.2147/ott.s287811
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Iron Metabolism-Related <em>SLC22A17</em> for the Prognostic Value of Gastric Cancer</p>

Abstract: Purpose Gastric cancer (GC) is a type of malignant cancer with a poor prognosis. The iron’s metabolism plays an important role in the process of GC. The aim of this study was to evaluate the effectiveness of SLC22A17 , associated with iron metabolism, in predicting the prognosis of GC patients. Materials and Methods We analyzed genes related to iron metabolism of gastric cancer mRNA-seq data from TCGA database. We identified an iron metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Two authors have also reported that SLC22A17 could be a prognosis biomarker of gastric cancer. Specifically, SLC22A17 was identified as a prognosis gene which may affect immune cell infiltration and iron metabolism in gastric (Hu C. et al, 2018;Wang et al, 2020;Wei et al, 2020). Although these two genes have been reported to be involved in gastric cancer, the specific mechanism of their regulation of gastric cancer is still unclear, which needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Two authors have also reported that SLC22A17 could be a prognosis biomarker of gastric cancer. Specifically, SLC22A17 was identified as a prognosis gene which may affect immune cell infiltration and iron metabolism in gastric (Hu C. et al, 2018;Wang et al, 2020;Wei et al, 2020). Although these two genes have been reported to be involved in gastric cancer, the specific mechanism of their regulation of gastric cancer is still unclear, which needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies reported that TME regulates the expression of LCN2, SLC22A17, and MMP9, which, in turn, modify the TME dynamism demonstrating a reciprocal modulation (Kessenbrock et al, 2010;Candido et al, 2016a;Wei et al, 2020;Crescenzi et al, 2021). This crosstalk is mediated Frontiers in Cell and Developmental Biology frontiersin.org by several chemokines, cytokines, and fibrillar proteins that activate the transcription of LCN2, SLC22A17, and MMP9 (Chinni et al, 2006;Iannetti et al, 2008;Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…COAD gene expression profiles and corresponding clinical information were downloaded from the TCGA database ( n = 512) and GEO database (GSE39582, n = 576). Seventy iron metabolism-related genes are listed in Supplementary Table S1 , which were derived from a previous study ( Wei et al, 2020 ). The GSE39582 dataset was used to validate the established signature.…”
Section: Methodsmentioning
confidence: 99%